Properties of Strain-Gauge Load Cells Applied for Stator Reaction Measurement - Lubomir Miklanek (Communications - Scientific letters of the University of Zilina, 2009)
This contribution deals with experience with the measurement of the stator reaction of the dynamometer using load cells. Originally, the stator reaction had been measured using a balance mechanism. Within the framework of the author’s research, it was necessary to improve the accuracy of torque measurement of the dynamometer. To accomplish this requirement, the old balance mechanism was replaced by a straingauge load cell. Two various types of the load cells were applied in order to arrange the measuring range to the expecting range of values of the torque. During the calibration, hysteresis in voltage output of the both applied load cells was observed. The maximal value of the hysteresis was about 0.5 % of the measured range of both of the load cells. Moreover, a certain temporary-plasticity of both of the load cells occurred.